2016
DOI: 10.2175/106143015x14362865226932
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Oxyanions from Industrial Wastewater using Perlite‐Supported Magnetite

Abstract: Most studies on oxyanion adsorption focus on their removal from synthetic solutions. It is often claimed that the considered adsorbents can be used to treat real (industrial) wastewaters, but this is seldom tested. Perlite-supported magnetite was characterized first by determining its specific surface area, magnetite content and by examining the coating. Tests on a synthetic solution showed that at the ideal pH values (pH 3 to 5), the order of adsorption is Mo(VI) > As(V) > Sb(V) > Cr(VI) > Se(VI). Most oxyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Real‐world environmental systems and conditions are complex (Huang et al, 2006; ; ; Qin et al, 2007; Verbinnen et al, 2016; Wang et al, 2014). In order to ascertain anaerobic biotransformation of RDX and HMX in the presence of nitrate‐sulfate mixture, different mixing conditions were used to assess their effects on the anaerobic biotransformation process.…”
Section: Resultsmentioning
confidence: 99%
“…Real‐world environmental systems and conditions are complex (Huang et al, 2006; ; ; Qin et al, 2007; Verbinnen et al, 2016; Wang et al, 2014). In order to ascertain anaerobic biotransformation of RDX and HMX in the presence of nitrate‐sulfate mixture, different mixing conditions were used to assess their effects on the anaerobic biotransformation process.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption experiments were performed with zeolite-and perlite-supported magnetite, prepared as described by Verbinnen et al (2012Verbinnen et al ( , 2013bVerbinnen et al ( , 2015. The adsorbents were saturated with Mo by contacting them with 50 mg/l Mo(VI) solutions.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…(1.5 g/l adsorbent, 24 h contact time at 160 rpm, pH 2.9) used for the adsorption experiments were selected based on the knowledge gained in previous research (Verbinnen et al, 2012(Verbinnen et al, , 2013b(Verbinnen et al, , 2015. The adsorbents were recuperated from the solution by filtering them over a paper filter.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of Verbinnen et al (2016) showed that perlite-supported magnetite is suitable for treating real wastewaters. It can remove several oxyanions simultaneously from the considered industrial wastewater.…”
Section: Introductionmentioning
confidence: 99%